Analysing the preferred characteristics of frontline employees dealing with customer complaints: a cross-national Kano study - Thorsten Gruber; Ibrahim Abosag; Alexander E. Reppel; Isabelle Szmigin (2011)
Purpose – This paper seeks to use the Kano model to gain a deeper understanding of attributes of effective frontline employees dealing with customer complainants in personal interactions. Previous research revealed that excitement factors deteriorate to basic factors over time. This research aims to investigate whether the same phenomenon holds true for attributes of service employees. Design/methodology/approach – Data were collected using Kano questionnaires from 272 respondents with complaining experience in the UK and Saudi Arabia, these being two countries at different stages of service sector development. Findings – The analysis of the Kano questionnaires for the UK reveals that complaining customers take the contact employee's ability to listen carefully for granted. The Kano results for Saudi Arabia clearly indicate that complaining customers are (still) easier to delight than their UK counterparts. Research limitations/implications – Even though the study has a sample size similar to several existing Kano studies, future research studies could still use larger probability samples that represent the broader (complaining) consumer population in the selected countries. Practical implications – If companies know what complaining customers expect, frontline employees may be trained to adapt their behaviour to their customers' underlying expectations. For this purpose, the paper gives several suggestions to managers to improve active complaint handling and management. Originality/value – The study adds to the understanding of effective complaint handling. The findings are the first to show that employee factors that are performance factors in a highly developed service economy can still delight customers in a less developed service economy.